Studi Literatur : Gaya Kepemimpinan Transformasional dan Motivasi Kerja - Eny Machsusiyah Zin; Saidati Nor Wildana; Mochammad Isa Anshori (CV. Aksara Global Akademia, 2023)
In this age of globalization there is much competition between the work world and organizations for change to be more innovative and competitive. So some organizations must have great leaders who can motivate their subordinates and be able to oversee employee performance. This study has a purpose to explain a leader's transformational leadership style and work motivation. The research is qualitative. Data collection techniques include listening attentively and recording important information to do data analysis through data reduction, data display, and deduction through previous literature and study discoveries.